Pemanfaatan Rumah Adat Tongkonan sebagai Pusat Peningkatan Literasi dan Numerasi bagi Siswa SD di Wilayah Pangala’ Utara - Tammu, Rahma Gusmawati; Palimbong, Stefani Marina; Pompeng, Olivia Devi Yulian; Pali, Elisabet; Biringkanae, Astriwati (Amare, 2023)
Indonesia is currently ranked sixty-second out of seventy countries, this situation has forced the government to issue new breakthroughs to improve reading and numeracy skills by building several libraries in each region, the government is also working with writers and publishers to make reading books more interesting. and educative. Literacy is the ability to read, write, speak, listen, count and be able to provide information and be able to interact with others. The mentoring for learning to read and count is carried out for students at SDN 2 Rindingallo as an effort to teach children to read and count so that students are more competent in reading and counting. The method used is with study assistance in small groups around the tongkonan traditional house. The results of the service show that through the use of the tongkonan traditional house, elementary school students in the vicinity of the traditional house show an increase in reading and arithmetic skills. The presence of tongkonan in every place in North Pangala' functions as a place for learning and playing activities. Through this activity, the function of the tongkonan is not only as a place to live but also as a place to acquire knowledge.